Heart rate variability analysis in comorbid insomnia and sleep apnea (COMISA) - Adrián Martín-Montero; Fernando Vaquerizo-Villar; Clara García-Vicente; Gonzalo C. Gutiérrez-Tobal; Thomas Penzel; Roberto Hornero (Scientific Reports)
Abstract Obstructive sleep apnea (OSA) and insomnia are the two most prevalent sleep disorders, often co-occurring in a condition termed comorbid insomnia and sleep apnea (COMISA). While autonomic nervous system (ANS) dysfunction resulting from each of these disorders has been separately established through heart rate variability (HRV) analysis, the specific overnight ANS alterations due to COMISA have not been explored. This study aims to characterize nocturnal ANS alterations attributable to COMISA through time and frequency HRV analysis, distinguishing them from those of isolated insomnia or OSA. A total of 5,335 electrocardiograms from the Sleep Heart Health Study (SHHS) dataset were included in this research. Based on overnight polysomnography and sleep questionnaires, participants were categorized into No-OSA (2,738 subjects), Insomnia (190 subjects), OSA (2,260 subjects), or COMISA (147 subjects) groups. Classic time and frequency HRV features, along with specific frequency measures, were computed to characterize HRV behavior throughout the whole night, in both wakefulness and sleep periods. The analysis revealed that COMISA-specific ANS dysfunction manifests as reduced parasympathetic activity during wakefulness and heightened sympathetic activation during sleep. While primary ANS dysfunctions seem to result from recurrent apneic events affecting frequency features present in both OSA and COMISA, insomnia significantly alters mean heart rate during sleep, thus being the only feature distinguishing these two conditions. In conclusion, the combined effects of OSA and insomnia induce specific ANS dysfunction at night, highlighting the need for further HRV studies to better understand the impact of COMISA on ANS and its cardiovascular implications. Clinical trial registration: The clinical trial identifier of the original SHHS database is NCT00005275, https://sleepdata.org/datasets/shhs .